Vibration Analysis of Carbon Nanotube Through Finite Element Method - Saini, Davinder (My University, 2012)
The primary motivation of the current research focuses on the ability to create simplified models that can accurately predict the structural and vibrational response of carbon nanotube structures undergoing different types of loading conditions. We have created a general process to make the carbon nanotube structures in different simulation software to do the finite element modeling and analysis. In this way, the mechanical characteristics regarding single-walled carbon nanotubes (SWCNTs) through Finite element modeling are computed. A simplified finite element model is created for different types of SWCNTs & MWCNTs with varying input parameters like Charity, tube-length, tube-diameter and the geometries of the nanotubes are also altered through various beam cross-section employed for the construction of the C-C bonds. The current work contributes to the generation of different model responses to monitor the vibration signatures employing a wide range of parameter values and comparison of the results with the existing research. The ability to introduce variability in the parameters and boundary conditions without altering the capabilities and computational time in the model represents the main contribution of the thesis from the mechanical component. ANSYS Software is used to do the finite element analysis of carbon nanotubes and PAYTHON language is used to generate the coordinates and the bonds for the ANSYS MECHANICAL APDL solver. Findings explaining the output from the mechanical simulations are summarized. Furthermore, conceptual contributions for future work are listed to develop models capable of physically interpreting the characteristics of SWCNTs & MWCNTs.
Master of Engineering (Production and Industrial Engineering)
Keywords: CNT, Nano Materials; FEM, Vibration Analysis